PERBANDINGAN HASIL PENGUKURAN EORTC QLQ-C30 DENGAN WHOQOL-BREF UNTUK MENGUKUR KUALITAS HIDUP PADA PASIEN KANKER: TELAAH LITERATUR - Amalia Nur Aqmarini; Dewi Gayatri; Tuti Nuraini; Yodang Yodang (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2022)
Comparison of EORTC QLQ-C30 and WHOQOL-BREF Measurement Results to Measure Quality of Life in CancerPatients: A Literature Review. It is important for nurses to carry out assessments and evaluate the condition of cancer patients, one of them by measuring their quality of life. The aim of this literature review is to identify the results of measurements of quality of life in cancer patients using EORTC QLQ-C30 and WHOQOL-BREF. Method: Using the PRISMA principle by searching journals through databases from ProQuest, CINAHL, PubMed, and Google Scholar conducted from June - July 2020. Article search is limited from 2010-2020. Assessment of journal article quality using the Joanna Briggs Institute (JBI) checklist. Results: Of 952 journals found, there are 14 journals that fit the research criteria. Quality of life scores measured by EORTC QLQ-C30 are higher than those measured by WHOQOL-BREF. EORTC QLQ-C30 and WHOQOL-BREF have different measurement aspects. Researchers recommend using the EORTC QLQ-C30 to measure the quality of life in cancer patients.